Accountability of Perpetrators of Criminal Acts of Business Fraud Using Deception (Study Decision Number: 130/Pid.B/2023/PN Kbu) - Maharani, Yopi; Baharudin, Baharudin; Satria, Indah (CV. Rayyan Dwi Bharata, 2024)
The era of globalization is a period where economics, technology, culture and politics throughout the world are increasingly connected and influence each other. The development of the times and the spread of social phenomena that occur on this earth never end in line with the social developments and dynamics that occur in society. This social phenomenon is called a criminal act. There are many criminal acts of fraud occurring in various forms and their development is increasingly high and complex, one of which is business fraud by deception. The crime of fraud itself is regulated in Article 378 of the Criminal Code. The problem in this research is what are the factors that cause committing criminal acts of business fraud by deception and what is the responsibility of perpetrators of criminal acts of business fraud based on Decision Number 130/Pid.B/2023/PN Kbu. The research method used in this research is a normative juridical approach and an empirical approach. This normative approach is carried out by viewing legal issues as rules that are considered appropriate to normative juridical research. Normative juridical research is carried out by means of literature studies on theoretical matters, namely an approach carried out by examining legal sources, legal principles and opinions of scholars as well as applicable laws and regulations. The Empirical Approach is an approach carried out through direct research on the research object by means of observation and interviews related to the research problem. The results of this research show that the factors causing the perpetrator to commit the crime of business fraud by deception are based on three factors, namely economic factors, opportunity factors and individual factors who often tell lies, both of which are the main causes of the defendant committing this act. The presence of false speech makes it seem as if the defendant is telling the truth, which creates trust or confidence in other people and interest, thereby causing the victim to be moved to hand over their property. Then the responsibility of the perpetrator of the criminal act of business fraud by deception is based on lying words that make other people hand over their property or objects resulting in the criminal act of fraud. In this case, the defendant has also been arrested by members of the North Lampung Police. The prosecutor as public prosecutor imposed charges on the defendant in the form of imprisonment for 3 (three) years and 10 (ten) months, which the judge then sentenced to prison for 3 years and 6 months as stated in Decision Number 130/Pid.B/2023/PN Mrs. The author's advice is aimed at ordinary people who want to carry out business activities so that they can be more thorough and understand first the partners they are going to do business with, starting from their origins, environment and experience in that field. Don't be immediately tempted by results that you won't necessarily get because it could be detrimental to yourself. The government/officials and all elements of society can strengthen supervision over business, as well as increase law enforcement against fraudulent business practices. This includes cooperation between law enforcement agencies, and other relevant agencies. Encourage the participation of all elements of society in reporting in order to prevent criminal acts of business fraud. By taking these steps, the government can play an important role in protecting prospective business actors.